Influence of cotton plant on development of Aphis gossypii Glover (Homoptera: Aphididae) - Elégbédé, M.T.; Glitho, I.A.; Akogbéto, M.; Dannou, E.A.; Mehinto, J.T.; Douro-Kpindou, O.K.; Tamò, Manuele (OMICS Publishing Group, 2014)
Aphis gossypii Glover (Homoptera: Aphididae) is one of the most important cotton pest in Benin. Experiments were carried out to determine population growth parameters of this pest and to compare its performance when feeding on detached leaves as opposed to the whole plant at constant temperature of 27 ± 1°C and 70 ± 5% of relative humidity. Results indicate that A. gossypii developed through four development stages with a mean development cycle of 4.38 ± 0.067 days. The doubling time of the aphid population was higher on whole plants (2.25 ± 0.02 days) than on detached leaves (1.91 ± 0.02 days). Similarly, the reproduction rate (Ro) of A. gossypii was lower on whole plants (16.023 ± 1.32) than on detached leaves (33.35 ± 1.68). Development, survivorship and reproduction of the aphid were negatively impacted by whole cotton plants, suggesting the possible induction of defence mechanisms.